Development of Interactive Learning Media in Economic Learning to Increase Student Interest in Learning - Taufiqurrahman*, Taufiqurrahman; Habib, Mustafa; Siregar, Zulham (Riwayat: Educational Journal of History and Humanities, 2023)
Education is the primary need of every human being that can improve human dignity and dignity itself. Moreover, in the 21st century, education faces a severe challenge, namely the challenge of globalization, which requires every human being to master knowledge and technology, for those who do not have education, they will naturally be excluded from global competition. One of the steps that can be taken to advance the education sector is by innovating in the delivery of learning materials. This research aims to; 1) Developing interactive learning media in economic learning to increase the interest in learning of grade X students of Stabat Preparation High School; 2) Knowing the response of students to the use of interactive learning media in economic learning increases the interest in learning of grade X students of Stabat Preparation High School. This research is a Research and Development (RD) research that adopts the development of Borg Gall. The subjects in this study were grade X students of Stabat Preparatory High School with data collection instruments used in the form of questionnaires given to media experts, material experts, and educators in the field of economic studies to test the quality of interactive learning media in economic learning and student response questionnaires to determine the interest and response of students to the learning media developed. The type of data produced is qualitative data that is analyzed with assessment category criteria guidelines to determine product quality.